2022
DOI: 10.1155/2022/9919542
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Use of Complementary Alternative Medicines among Inflammatory Bowel Disease Patients: Results from a Single Center Survey

Abstract: Background. Complementary and alternative medicines (CAMs) are used by patients with chronic disorders, such as inflammatory bowel disease (IBD), with a desire to manage their disease. Methods. Patients visiting an IBD outpatient clinic and infusion unit in a tertiary referral center were surveyed through an anonymized Dutch version of the international questionnaire to measure the use of CAMs. Results. Of the 467 IBD patients who responded to the survey, 41.8% ( n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Use of strict and standardised medium- and long-term outcomes in line with “treat-to-target” strategies as adopted by the STRIDE19 118 119 and SPIRIT37 guidelines.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of strict and standardised medium- and long-term outcomes in line with “treat-to-target” strategies as adopted by the STRIDE19 118 119 and SPIRIT37 guidelines.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…This is where policy makers and healthcare funders could play a crucial role in driving this research forward, next to providing the necessary framework for recognition and reimbursement of proven therapies. For patients, patient organisations and clinicians, it will be important to reach out and openly discuss treatment goals, treatment options and the current CAMs patients are using (if relevant) 19. In order to do so, clinicians should get adequately informed and confident with the evidence on these kinds of treatments.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Notably, a significant proportion (70.8%) of IBD patients using green tea as a complementary and alternative medicine have reported its efficacy. 10 Previous studies showed promising outcomes for various tea components, such as tea polyphenols, 7 green tea polyphenols, 11 green tea polysaccharides, 12 epigallocatechin-3-gallate (EGCG), 13,14 black tea polysaccharides, 12 theaflavin-3,3 0digallate (TFDG), 15 selenium-containing tea polysaccharides 16 and Fuzhuan brick tea polysaccharides. 17 These tea compounds have demonstrated favorable therapeutic effects with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Tea has been recognized as a potentially protective dietary factor, particularly in Asian populations where studies have reported a negative association between tea consumption and IBD 9 . Notably, a significant proportion (70.8%) of IBD patients using green tea as a complementary and alternative medicine have reported its efficacy 10 . Previous studies showed promising outcomes for various tea components, such as tea polyphenols, 7 green tea polyphenols, 11 green tea polysaccharides, 12 epigallocatechin‐3‐gallate (EGCG), 13,14 black tea polysaccharides, 12 theaflavin‐3,3′‐digallate (TFDG), 15 selenium‐containing tea polysaccharides 16 and Fuzhuan brick tea polysaccharides 17 .…”
Section: Introductionmentioning
confidence: 99%